Effect of Dragon Fruit Juice Addition on Changes in Peroxide Numbers and Acid Numbers of Used Cooking Oil - Sri Adelila Sari; Tika Rahayu Putri; Muhammad Rudi AR (Indonesian Journal of Chemical Science and Technology (IJCST), 2019)
Many foods from Indonesia are cooked through the frying process using cooking oil. Good cooking oil is oil that has a low amount of peroxide and acid. The purpose of this study was to find the effect of adding dragon fruit juice (Hylocereus undatus)to peroxide numbers and acid numbers in used cooking oil. Peroxide numbers were measured using the iodometry method, whereas acidic numbers were carried out by the acid-base method. The results of this study indicated that after the addition of dragon fruit juice the peroxide number was dropped to 2.4 meg / kg, whereas in acid numbers an acid number was increased to 6.08 percent.